A systematic review on methods used in health education intervention on anaemia in pregnancy - Hassan, Hasneezah; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Anaemia is a common health problem during pregnancy, which leads to adverse health consequences to both mothers and infants. Health education is an important strategy in preventing anaemia. It’s success to improve haemoglobin level depends on the methods and design. This review aimed to identify the methods used and the effectiveness of health education intervention in improving anaemia in pregnancy. A systematic review of studies published in MEDLINE, CINAHL, Science Direct and PubMed from January 2010 to April 2017 was conducted using various keywords. Initial search revealed 274 articles, which later reduced to eight after being screened for inclusion criteria that consist of intervention study and involving pregnant women as participants. Health education intervention program with various delivery methods were proven to significantly reduce the prevalence of anaemia in pregnancy. Group discussion, health talk, poster presentation and educational pamphlet were common methods used in health education intervention.